Metabolic effects of prolactin - Pirchio, Rosa; Graziadio, Chiara; Colao, Annamaria; Pivonello, Rosario; Auriemma, Renata S. (Frontiers in Endocrinology, 2022)
Over the last years, the metabolic role of PRL has emerged. PRL excess is known to promote weight gain, obesity, metabolic syndrome, and impairment in gluco-insulinemic and lipid profiles, likely due to the suppression of physiologic dopaminergic tone. Prolactin receptors and dopamine receptors type 2 have been demonstrated to be expressed on both human pancreatic β-cell and adipocytes, supporting a key role of prolactin and dopamine in peripheral metabolic regulation. Medical treatment with the dopamine agonists bromocriptine and cabergoline has been demonstrated to decrease the prevalence of metabolic syndrome and obesity, and significantly improve gluco-insulinemic and lipid profiles. In hyperprolactinemic men with concomitant hypogonadism, correction of hyperprolactinaemia and testosterone replacement has been proven to restore metabolic impairment. In turn, low prolactin levels have also been demonstrated to exert a detrimental effect on weight gain, glucose and lipid metabolism, thus leading to an increased prevalence of metabolic syndrome. Therefore, PRL values ranging from 25 to 100 μg/L, in absence of other recognizable pathological causes, have been proposed to represent a physiological response to the request for an increase in metabolic activity, and nowadays classify the so-called HomeoFIT-PRL as a promoter of metabolic homeostasis. The current review focuses mainly on the effects of hyperprolactinemia and its control by medical treatment with DAs on the modulation of food intake, body weight, gluco-insulinemic and lipid profile. Furthermore, it provides the latest knowledge about the metabolic impact of hypoprolactinemia.